Brugia Malayi: Depletion of Glutathione by Buthionine Sulfoximine - Ayman Hussein (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
Glutathione is an intracellular reducing agent. It is synthesized by a two-step reaction catalyzed by ?-glutamylcysteine synthetase (?GCS) and glutathione synthetase. ?GCS, which is the rate limiting enzyme in the synthesis of glutathione, is inhibited specifically by buthionine sulfoximine (BSO). The enzyme was partially purified from the parasitic nematode Brugia malayi, the causative agents of lymphatic filaraiasis. BSO inhibits the enzyme activity in an irreversible manner. The Brugia enzyme was found to be 24-fold more sensitive to BSO than its mammalian counterparts. The inhibitor was also found effective in depleting the glutathione contents of the parasites with low concentration. The results may conclude that ?GCS is a potential target for the development of drugs against filariasis.